Karnataka’s smart, new solar pump policy for irrigation - Shah, Tushaar; Verma, S.; Durga, N. (2014)
The runaway growth in states of subsidised solar pumps, which provide quality energy at near-zero marginal cost, can pose a bigger threat of groundwater over-exploitation than free power has done so far. The best way to meet this threat is by paying farmers to "grow" solar power as a remunerative cash crop. Doing so can reduce pressure on aquifers, cut the subsidy burden on electricity companies, reduce the carbon footprint of agriculture and improve farm incomes. Karnataka's new Surya Raitha policy has ken a small step in this direction.